Planning Energy Efficient and Livable Cities - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2015)
The world's urban population is expected to increase by about 2.7 billion by 2050.Virtually all of the increased population will be in developing countries, leading to massive needs for new and improved housing and urban infrastructures (UNDESA 2012). The planning and design of these new developments will reshape or create new urban landscapes with significant implications for energy consumption, infrastructure costs, as well as the livability and social and economic resilience of cities. Studies of cities around the world indicate that a city's livability and its level of energy use are closely linked to its physical form, namely the spatial distribution and dimensions of buildings, streets, and parks, as well as the spatial coordination of residences, jobs, social services, and environmental amenities.